2018
DOI: 10.5483/bmbrep.2018.51.8.089
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling identified IL-8 as a regulator of homotypic cell-in-cell formation

Abstract: Homotypic cell-in-cell (CIC) structures forming between cancer cells were proposed to promote tumor evolution via entosis, a nonapoptotic cell death process. However, the mechanisms underlying their formation remained poorly understood. We performed a microarray analysis to identify genes associated with homotypic CIC formation. Cancer cells differing in their ability to form homotypic CIC structures were selected for the study. Association analysis identified 73 probe sets for 62 candidate genes potentially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…These data suggest that entosis represents a safety mechanism to remove ‘abnormal’, detached cells from a tissue. Other activators of entosis include reactive oxygen species, methylselenoesters, epidermal growth factor, IL-8 and serum [813] (Figure 1A), some of which might trigger entosis simply by causing mitosis or apoptosis.…”
Section: The Formation Of Cic Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that entosis represents a safety mechanism to remove ‘abnormal’, detached cells from a tissue. Other activators of entosis include reactive oxygen species, methylselenoesters, epidermal growth factor, IL-8 and serum [813] (Figure 1A), some of which might trigger entosis simply by causing mitosis or apoptosis.…”
Section: The Formation Of Cic Structuresmentioning
confidence: 99%
“…A prerequisite for entosis is an interaction between the two cells, which is mediated through the catenin and cadherin adhesion molecules [3,13,14]. To form a CIC structure, the driver cell needs to be relatively rigid, whereas the external cell requires high deformability to extend its membrane all the way around the invading cell [15].…”
Section: The Formation Of Cic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several chemokines, cytokines and angiogenic factors produced by neutrophils may result in inflammatory cell recruitment and activation that crucially impact the tumor microenvironment, which could facilitate tumor cell proliferation, microvascular regeneration and tumor progression (9,14,15). The formation of CIC structure in tumors is a functional result of active intercellular interactions within heterogeneous tumor microenvironments, which is driven by a set of core molecular elements (16,17) that are regulated by multiple factors, such as cholesterol and IL-8 (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction 49 Cell division via mitosis is strictly regulated to ensure the production of healthy daughter 50 cells. During mitosis, correct segregation and distribution of genetic materials into daughter cells 51 rely on proper activation of spindle assemble checkpoint (SAC) (Musacchio, 2015;Sivakumar & Multiple factors, including CDKN2A (Liang et al, 2018), IL-8 (Ruan et al, 2018a) and membrane 73 cholesterol and lipids (Ruan et al, 2018b), that affects RhoA signaling were recently identified as 74 important regulators of entotic CIC formation. Although initially viable, majority of the internalized 75 cells die non-autonomously with the assistance of outer host cells (Florey et al, 2011).…”
Section: Main Text 48mentioning
confidence: 99%